MEDIA PEMBELAJARAN BERBASIS GAME ULAR TANGGA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Dhinda Dewy Herliana; Nikmatilah Riskiyana; Zakkiyah Zakkiyah (Kampus Akademik Publiser, 2025)
Learning media is an important tool in educational success, which teachers use to achieve learning goals. Interesting learning media can overcome student boredom, such as through the application of game-based media, for example the snakes and ladders game. In developing snakes and ladders learning media, preparation of materials, game rules, group division, and time allocation are required. The implementation of this media has been proven to be able to increase student learning motivation, encourage activeness, and higher learning enthusiasm.